Spousal role and caregiver burden in HIV affected families in Anhui Province, China. Issue 10 (3rd October 2017) - Hsieh, Julie; Li, Li; Lin, Chunqing; Luo, Sitong; Ji, Guoping
ABSTRACT: This study examined the burden experienced by various roles of family caregivers of people living with HIV (PLH), in particular spouses vs. non-spouses. A total of 475 family members of PLH were recruited from Anhui Province, China. Participants responded to a survey using the Computer Assisted Personal Interview method. The assessment collected data on demographic characteristics and their perceived caregiver burden, which was compared between spouses and non-spouses. Multiple regression models were built to identify factors associated with caregiver burden. About 64.4% of our study participants were female and the mean age was 42.1 years. Among various relationships to PLH, almost half reported being a spouse. Spouses reported significantly higher caregiver burden than non-spouses. In addition, older age and lower family income were significantly associated with higher level of caregiver burden. Among the subsample of spouses, significantly higher level of caregiver burden was identified among wives. Future studies should give special consideration to address the needs of female spouses in order to reduce their caregiver burden.